Vietnam: políticas públicas en ciencia, tecnología e innovación - Lemus Delgado, Daniel Ricardo (El Colegio de México, 2020)
This article analyzes Vietnam’s science, technology and innovation policies. The introduction focuses on the country’s economic transformation since the Dổi mới reforms and I discuss how these developments have introduced a structural change. The argument is that Vietnam’s economic transformation has framed scientific and technological activities. In addition, I examine the scientific and technological sector’s evolution and its connection to the creation of a National Innovation System. I also evaluate the performance of the scientific and technological sector within the international context. Finally, I introduce some reflections about the importance of strengthening science, technology and innovation as a key for the development of Vietnamese society.